2000
DOI: 10.1034/j.1399-6576.2000.440204.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of intravenous clonidine on propofol or thiopental induction

Abstract: The study evaluated the effects of premedication with intravenous clonidine on thiopental or propofol requirements for induction and haemodynamic changes associated with both induction and endotracheal intubation. Clonidine administered intravenously before induction of anaesthesia reduced propofol or thiopental requirements. The association of clonidine and propofol caused, after injection of the induction drug, a decrease in mean arterial pressure which was significantly greater than with thiopental. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…There were no statistically significant changes in heart rate observed at the successive stages of induction. However, the tendency towards heart rate increases associated with direct laryngoscopy and endotracheal intubation is visible, which is consistent with the findings of many stud- ies [20,30] and results from stimulation of the sympathetic nervous system. Interestingly, during anaesthesia with propofol, the induction causes increases in the concentration of norepinephrine [4].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There were no statistically significant changes in heart rate observed at the successive stages of induction. However, the tendency towards heart rate increases associated with direct laryngoscopy and endotracheal intubation is visible, which is consistent with the findings of many stud- ies [20,30] and results from stimulation of the sympathetic nervous system. Interestingly, during anaesthesia with propofol, the induction causes increases in the concentration of norepinephrine [4].…”
Section: Discussionsupporting
confidence: 90%
“…The use of a dose of propofol for the induction of anaesthesia has not fully ensured the stability of systemic circulation. Haemodynamic imbalance often accompanies the induction of anaesthesia, which is confirmed by the results of experimental [18] and clinical studies [20,29].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Imai Y, Mammoto T, et al who investigated the effects of pre-anaesthetic oral clonidine (150 mcg) on Propofol/Fentanyl anaesthesia, reported a reduction of 40% in the propofol requirements. Similar findings were also reported by Hideyuki Higuchi et al, Fehr et al [35][36][37] Patients in group CL were significantly more sedated than the patients in group C, (P < 0.005) which could be explained by the action of clonidine on sleep promoting pathways and locus coeruleus. However, with 150 mcg of clonidine the mean sedation scores in clonidine group were never more than 2 before induction i.e the patients were 'awake but uncommunicative'(as per the sedation score).…”
supporting
confidence: 79%
“…Marinangeli F et al studied the haemodynamic effects of intravenous clonidine on thiopental induction. In this study the dose of thiopentone required for induction in control group was 5.80 mg/kg and in clonidine group with 3µg/kg clonidine was 3.8 mg/kg showing reduction of 34% compared to control (p<0.05) [14] . Above authors have found statistically significant reduction of thiopentone dose required for induction in the clonidine group (p<0.05), which concurs with our study.…”
Section: Discussionmentioning
confidence: 99%